Nurse’s Perspective in the Implementation of Family Centered Care in PICU NICU - Mariyam, Mariyam; Utami, Minarti Dyan; Samiasih, Amin; Alfiyanti, Dera; Hidayati, Eni (Universitas Aisyah Pringsewu, 2022)
Implementation of Family Centered Care (FCC) in pediatric critical care has many obstacles and challenges, so the role of nurses as facilitators and enforcers of rules is difficult in implementing FCC. The purpose of this study was to determine the perspective of nurses in the application of FCC in the NICU PICU . The study was conducted in January-February 2022 in PICU NICU at Dr Kariadi Hospital Semarang with a quantitative descriptive design method and a consecutive sampling technique of 52 samples. The results showed that the nurse's perspective in the implementation of FCC in NICU PICU was 90.4% good. The element of sharing information with parents is 100% good, the element of hearing a parental voice is good 98%, the element of making decisions with parents is good 96%, the element of individual communication is good 94%, and the element of negotiating roles is good 63%. FCC in critical care children prioritizes partnerships between parents and health workers, where the role of parents can be negotiated in the implementation of FCC according to the clinical condition of the child and the characteristics of the parents. Nurses are expected to improve skills during resuscitation so that the implementation of FCC in the role negotiation elements can be carried out properly. Abstrak: Implementasi Family Centered Care (FCC) dalam keperawatan kritis anak mempunyai banyak hambatan dan tantangan, sehingga peran perawat sebagai fasilitator dan penegak aturan kesulitan dalam pengimplementasian FCC. Tujuan dari penelitian ini adalah untuk mengetahui perspektif perawat dalam penerapan FCC di PICU NICU. Penelitian dilakukan pada bulan Januari-Februari 2022 di PICU NICU RSUP Dr Kariadi Semarang dengan metode kuantitatif, desain deskriptif dan teknik consecutive sampling sebanyak 52 sampel. Hasil penelitian menunjukkan bahwa perspektif perawat dalam penerapan FCC di PICU NICU adalah baik 90,4 %. Elemen berbagi informasi dengan orang tua baik 100%, elemen mendengar keluhan dan menjawab pertanyaan orang tua baik 98%, elemen membuat keputusan dengan orang tua baik 96%, elemen komunikasi individual baik 94%, dan elemen negosiasi peran baik 63%. Family Centered Care (FCC) dalam keperawatan anak kritis mengedepankan kemitraan antara orang tua dan petugas kesehatan, dimana peran orang tua dapat dinegosiasikan dalam pengimplementasian FCC sesuai dengan kondisi klinis anak dan karakteristik orang tua. Perawat diharapkan dapat meningkatkan keterampilan saat tindakan resusitasi sehingga pengimplementasian FCC pada elemen negosiasi peran dapat terlaksana dengan baik.